ANALISA KEBUTUHAN AIR BERSIH DI KOTA MEDAN SUMATERA UTARA - Simanjuntak, Salomo; Zai, Eben Oktavianus; Tampubolon, Michael Halomoan (Jurnal Visi Eksakta, 2021)
The water that humans really need is good quality water, which is commonly known as clean water. Clean water is one type of water-based resource that is of good quality and is commonly used by humans for consumption or in carrying out their daily activities including sanitation. The most important thing is clean water is a basic human need which greatly affects human health. The stages in completing this Final Project are first to collect the required data from the Central Bureau of Statistics and BAPPEDA Medan City with literature reviews and ask questions directly to related parties about the required data. Then the calculation of the projected population in the city of Medan using the geometric, arithmetic method. The next stage is calculating the need for clean water in Medan City and calculating the maximum daily water needs and peak hours.